Intraspecific competition and water use efficiency in Quercus suber: evidence of an optimum tree density? (Trees, 2008)
The dehesa and montado agroecosystems seem to be water-stress induced structures and some authors have found evidence of a relationship between stand tree density and mean annual precipitation. In order to assess the ecophysiological responses of Quercus suber to increasing tree density and to evaluate if there was evidence of an ‘‘optimum tree density’’ with respect to mean annual rainfall in our study area, we established a tree-density gradient of 20, 40, and 60 trees ha -1 , coded D20, D40, and D60, respectively. Trees in D40 plots had higher speciﬁc leaf area (SLA) values and the highest water content. Both D20 and D60 trees had leaves with higher dry matter content (LDMC). The trade-off between SLA and LDMC was very strong and placed D40 trees as the least stressed, in terms of leaf anatomy. We also found differences in mean carbon isotope discrimination (D), between different density plots, as big as 1.25%. Again, D40 trees discriminated more against 13 C than the trees from D20 and D60 plots, which suggests a less conservative water use strategy, possibly deriving from greater water availability. The lower water retention in the D20 areas and the increased competition for water resources in D60 plots placed trees, in both areas, in a more stressful situation, regarding water availability. The D40 areas thus seemed to represent a more favourable environment for Q. suber in our montado. Therefore, the areas with 40 trees ha -1 suggest the existence of an optimum tree density with respect to annual rainfall in our site, and may represent a compromise between an increased retention of water resources and intraspeciﬁc competition.